Acute kidney injury and in-hospital mortality in patients with ST-elevation myocardial infarction of different age groups. (1st December 2021) - Cosentino, Nicola; Resta, Marta L.; Somaschini, Alberto; Campodonico, Jeness; Lucci, Claudia; Moltrasio, Marco; Bonomi, Alice; Cornara, Stefano; Camporotondo, Rita; Demarchi, Andrea; De Ferrari, Gaetano M.; Bartorelli, Antonio L.; et al.
Abstract: Background: Acute kidney injury (AKI) is a well-known complication of ST-elevation acute myocardial infarction (STEMI) with an adverse impact on prognosis. Since AKI develops more frequently in elderly patients, we hypothesized that its higher incidence in older STEMI patients might explain their increased in-hospital mortality. We assessed the relationship between AKI and in-hospital mortality in patients with STEMI of different age groups. Methods: We retrospectively evaluated 5136 STEMI patients treated with primary percutaneous coronary intervention (pPCI). We defined AKI as ≥0.5 mg/dl creatinine increase in the first 72 h. Patients were grouped according to age (<75 [ n  = 4040] or ≥ 75 [ n  = 1096] years). The primary endpoint was in-hospital mortality. Results: The incidence of AKI was 7%. It was 4.6% in patients <75 years and 15.1% in those ≥75 years ( P  < 0.0001). The overall in-hospital mortality was 4%. It was 2.6% and 8.5% in patients younger and older than 75 years, respectively (P < 0.0001). It was higher in AKI than in non-AKI patients, both in the overall population (27% vs. 2%) and in the two age groups (25% vs. 2% and 29% vs. 5% in younger and older patients, respectively; P  < 0.0001). The adjusted odds ratio of in-hospital mortality associated with AKI progressively decreased in parallel with increasing age decades (from 24.7 [95% CI 11.2–54.1] in patients <65 years to 3.9 [95% CI 1.6–9.7] in those >85 years). Conclusions: In STEMI patients treated with pPCI, AKI incidence and in-hospital mortality steadily increase with age. However, the prognostic impact of AKI is progressively reduced as age increases. Highlights: In STEMI, acute kidney injury (AKI) develops more frequently in elderly patients. In-hospital mortality steadily increase with age in STEMI patients. AKI carries a lower relative risk of in-hospital mortality in elderly patients than in younger ones.